2007
DOI: 10.2340/00015555-0185
|View full text |Cite
|
Sign up to set email alerts
|

Histamine, But Not Leukotriene C4, is an Essential Mediator in Cold Urticaria Wheals

Abstract: In addition to histamine, leukotriene C4 (LTC4) might also play a role in mediating cold urticaria wheals. To study the significance of LTC4 vs. histamine, 6 patients with cold urticaria were challenged with the ice cube test before and after ingestion of 10 mg cetirizine (antihistamine), 10 mg montelukast (leukotriene antagonist) or a combination of both drugs. Cetirizine diminished the cold-induced wheal by 50+/- 42%. Montelukast had no significant effect, and the combination of both drugs diminished the whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…Most types of urticaria, including chronic spontaneous urticaria and the majority of inducible urticarias, are mediated primarily by mast cell-derived histamine[20] which reaches very high concentrations due to the poor diffusibility of substances in the dermis. [2122] They are characterized by short-lived wheals ranging from a few millimeters to several centimeters in diameter which are accompanied by severe itching which is usually worse in the evening or night-time.…”
Section: Introductionmentioning
confidence: 99%
“…Most types of urticaria, including chronic spontaneous urticaria and the majority of inducible urticarias, are mediated primarily by mast cell-derived histamine[20] which reaches very high concentrations due to the poor diffusibility of substances in the dermis. [2122] They are characterized by short-lived wheals ranging from a few millimeters to several centimeters in diameter which are accompanied by severe itching which is usually worse in the evening or night-time.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms are usually limited to coldexposed skin areas, but extensive cold contact may result in generalized symptoms, such as headache, dyspnoea, hypotension and loss of consciousness (5,6). Hives are caused by histamine (7)(8)(9)(10) and other mediators, such as platelet-activating factor (PAF) and cytokines released from activated mast-cells, after exposure to cold triggering factors (1,2,(11)(12)(13)(14)(15)(16). To confirm the diagnosis cold stimulation standardized tests are mandatory.…”
mentioning
confidence: 99%
“…A pilot study of nettle- Burn injury (132) induced urticaria showed immediate discomfort and stinging pain but marginal histamine release and no leukotriene release (123). The absence of leukotriene release was directly confirmed in cold urticaria using microdialysis samples and indirectly by the absence of a clinical effect of montelukast, a leukotriene antagonist (124). recently, Kring Tannert et al (125) performed an elegant study showing normalisation of histamine release in the skin of patients with cold-test urticaria after successful cold desensitisation but the maintenance of its releasability to codeine treatment.…”
Section: Urticariamentioning
confidence: 96%